2007
DOI: 10.1080/10284150701250671
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endocannabinoid synthetic enzyme mRNAs is correlated with cannabinoid 1 receptor mRNA in the mouse brain

Abstract: The two principal endocannabinoids, N-arachidonoyl-ethanolamine (anandamide) and 2-arachidonoyl-glycerol (2-AG), are synthesized from arachidonic acid (AA) and AA is released as they are degraded. Therefore, the function of endocannabinoids is closely linked to AA, but the exact relationships have not been clarified, especially with respect to endocannabinoid metabolism. In the present study, oil rich in AA was administered (0, 100, 200 and 300 microl) orally to male mice for 7 days. Phospholipase D (PLD), fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is possible to consider that dietary LA itself may modulate EC biosynthesis. However, Tsuyama et al 13 reported that gene expressions of enzymes associated with EC metabolism were not altered, even though several doses of AA were given orally to mice. Therefore, we believed that the contribution of LA on EC production might not be strong.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible to consider that dietary LA itself may modulate EC biosynthesis. However, Tsuyama et al 13 reported that gene expressions of enzymes associated with EC metabolism were not altered, even though several doses of AA were given orally to mice. Therefore, we believed that the contribution of LA on EC production might not be strong.…”
Section: Discussionmentioning
confidence: 97%
“…(51), mice supplemented with 0.5 weight% of arachidonic acid for 58 days had dramatically increased brain levels of AEA. Dietary arachidonic acid (270 mg/day, corresponding to approximately 1 energy%/day) given for 7 days to mice did not affect the expression of CB 1 receptor or endocannabinoid enzymes (52). Another study found that feeding young mice 10 wt% fish oil for 6 weeks, a diet that is not relevant for humans in terms of the very high fish oil content, resulted in decreased levels of 2‐AG in the brain (53).…”
Section: Dietary Polyunsaturated Fatty Acids and Endocannabinoid Formmentioning
confidence: 99%